The background of the most successful venture capitalists - Castro, Francisco Nunes Pacheco De (2020)
This Work Project aims toconduct an exploratory analysis intowhether and to which degree socioeconomic variables can predict Venture Capital performance.Using Crunchbase’s database, tests were conducted to test for independence,both in the complete sample and incertain sub-samples. Gender, alma mater and academic field do not seem to be independent ofVC performance, with alower proportion of business majors and ahigher proportion of MBAs, sciences majors and women in topVC firms.The notable exceptions beingthe sub-samples with the highest average age, where women are less likely to work on top firms.